New arsenate minerals from the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia. VI. Melanarsite, K3Cu7Fe3+O4(AsO4)4. (2nd January 2018) - Pekov, Igor V.; Zubkova, Natalia V.; Yapaskurt, Vasiliy O.; Polekhovsky, Yury S.; Vigasina, Marina F.; Belakovskiy, Dmitry I.; Britvin, Sergey N.; Sidorov, Evgeny G.; Pushcharovsky, Dmitry Y.
Abstract: The new mineral melanarsite, K3 Cu7 Fe 3+ O4 (AsO4 )4, was found in the sublimates of the Arsenatnaya fumarole at the Second scoria cone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka Peninsula, Russia. It is associated with dmisokolovite, shchurovskyite, bradaczekite, hematite, tenorite, aphthitalite, johillerite, arsmirandite, As-bearing orthoclase, hatertite, pharmazincite, etc. Melanarsite occurs as tabular to prismatic crystals up to 0.4 mm, separate or combined in clusters up to 1 mm across or in interrupted crusts up to 0.02 cm × 1 cm × 1 cm covering basalt scoria. The mineral is opaque, black, with a vitreous lustre. Melanarsite is brittle. Mohs' hardness is ∼4 and the mean VHN = 203 kg mm –2 . Cleavage was not observed and the fracture is uneven. D calc is 4.39 g cm –3 . In reflected light, melanarsite is dark grey. Bireflectance is weak, anisotropism is very weak. Reflectance values [R1 –R2, % (λ, nm)] are 10.5–9.4 (470), 10.0–8.9 (546), 9.7–8.7 (589), 9.5–8.6 (650). The Raman spectrum is reported. Chemical composition (wt.%, electron microprobe) is K2 O 10.70, CaO 0.03, CuO 45.11, ZnO 0.24, Al2 O3 0.32, Fe2 O3 6.11, TiO2 0.12, P2 O5 0.07, As2 O5 36.86, total 99.56. The empirical formula, based on 20 O apfu, is (K2.81 Ca0.01 )∑2.82 (Cu7.02 Fe 3+ 0.95 Al0.08 Zn0.04 Ti0.02 )∑8.11 (As3.97 P0.01 )∑3.98 O20 . Melanarsite is monoclinic, C2/c, a = 11.4763(9), b = 16.620(2), c = 10.1322(8) Å, β = 105.078(9)°, V = 1866.0(3) Å 3 and Z = 4. The strongest reflections of the powder X-ray diffraction pattern [ d, Å(I)( hkl )] are 9.22(100)(110), 7.59(35)(1₃11), 6.084(17) (111), 4.595(26)(1₃31, 220, 2₃21), 3.124(22)(3₃31, 1₃51), 2.763(20)(400, 1₃52), 2.570(23)(043) and 2.473(16) (260, 2₃61, 350). Melanarsite has a novel structure type. Its crystal structure, solved from single-crystal X-ray diffraction data ( R = 0.091), is based upon a heteropolyhedral pseudo-framework built by distorted Cu(1–3)O6 and (Fe, Cu)O6 octahedra and As(1–3)O4 tetrahedra. Two crystallographically independent K + cations are located in the tunnels and voids of the pseudo-framework centring eight- and seven-fold polyhedra. The name reflects the mineral being an arsenate and its black colour (from the Greek μέλαν, black).